Re-establishing Class Privilege: The Ideological Uses of Middle and Working-Class Female Characters in Downton Abbey - Laetitia Kevers (Anglica. An International Journal of English Studies, 2017)
This paper argues that the British period drama Downton Abbey, which aired between 2010 and 2015 and encountered worldwide success, uses working class and middle-class female characters to promote the aristocracy and conservative ideas, while hiding behind historical accuracy and seemingly progressive patterns of behaviour. Through a close reading of four female characters, I will demonstrate how the series’ author, Julian Fellowes, uses the show to endorse his own political agenda, as a Conservative member of the House of Lords in the British Parliament.